Natural product derived algae polyelectrolyte membrane as well as preparation method and application thereof

By developing natural product-derived algae polyelectrolyte membranes, the problem of performance degradation in high temperature and low humidity environments is solved, and a high-performance, low-cost and environmentally friendly proton exchange membrane is achieved, which improves the performance and sustainability of direct methanol fuel cells.

CN119518044APending Publication Date: 2025-02-25JILIN AGRICULTURAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411480835.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing Nafion@ series membranes have degraded performance in high temperature and low humidity environments, poor dimensional stability, high preparation costs, and pose a potential threat to the environment and human health.

Method used

A natural product-derived algae polyelectrolyte membrane was developed, prepared by the synthesis method of sulfonated sodium alginate and diatomaceous earth, and a simplified process flow was adopted to reduce production costs.

Benefits of technology

The membrane exhibits superior performance over traditional Nafion@117 membranes in direct methanol fuel cells, improving open circuit voltage and maximum power density, reducing production costs, reducing environmental pollution, and simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518044A_ABST
    Figure CN119518044A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of direct methanol fuel cells, and provides a natural product derived algae polyelectrolyte membrane and a preparation method and application thereof.The preparation method comprises the steps that sulfonated sodium alginate and sulfonated diatomite are prepared, sulfonated sodium alginate powder is dissolved in deionized water to form a pouring solution, the sulfonated diatomite powder is added into the pouring solution, and the natural product derived algae polyelectrolyte membrane is obtained; and drying to form a film, soaking in a solution, heating and curing to obtain the product. The algae polyelectrolyte membrane based on a natural product is developed, the membrane shows performance superior to that of a traditional Nafion-coated 117 membrane in a direct methanol fuel cell, the production cost is remarkably reduced, the environmental pollution is reduced, the preparation process is simplified, toxic intermediate products are avoided, the problem of high methanol fuel permeability is effectively solved, and the membrane has a good application prospect. A new thought is provided for designing the proton exchange membrane which is high in performance, low in cost and environmentally friendly, and the method has important significance on high-value utilization of biomass resources, environmental protection and social sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of direct methanol fuel cells, and in particular relates to a natural product derived algae polyelectrolyte membrane and a preparation method and application thereof. Background Art

[0002] Direct methanol fuel cells are considered to be the most promising and environmentally friendly fuel cells due to their high energy density, convenient supply, abundant fuel sources, easy storage of methanol and low environmental pollution. Among them, the proton exchange membrane is the core component of direct methanol fuel cells, which plays the role of isolating methanol fuel and providing proton transfer channels. Its performance is directly related to the output power, service life, production cost and application prospects of direct methanol fuel cells.

[0003] The current commercial proton exchange membrane is based on Nafion @ The perfluorosulfonic acid membrane (PFSA) represented by the Nafion series membrane has good chemical stability and excellent proton conductivity and physical and chemical properties. @ It is a free radical initiated copolymer made of crystallizable hydrophobic tetrafluoroethylene (TFE) and perfluorinated vinyl ether with side chains terminated by perfluorosulfonic acid groups. The former gives it excellent structural integrity and chemical stability, while the latter gives them ideal proton conductivity when fully hydrated. However, Nafion @ The membrane also has several defects, which limit its wider application: (1) For fuel cells, in order to improve performance, the activity of reactants can often be increased by increasing the temperature, but the flexible main chain of Nafion @ The glass transition temperature of Nafion is only about 100°C. Operating at high temperatures can easily lead to a significant reduction in the dimensional stability of the membrane or even damage. (2) Nafion @ The membrane has insufficient water retention and is highly dependent on humidity. Its proton conductivity drops sharply as the relative humidity decreases. To maintain a high proton conductivity, the operating temperature of the battery cannot be higher than 100°C or lower than 0°C (boiling or freezing). This is not conducive to Nafion @ In practical applications, it can cope with sudden changes in temperature and humidity. (3) The high fluorine content makes Nafion @ The preparation cost is high and it also exacerbates the problem of environmental pollution. (4) Poor dimensional stability. Nafion @ The dry membrane size and its saturated state size at high relative humidity can differ by more than one time, which not only affects the performance of the battery, but can even cause serious fuel leakage and explosion. (5) The membrane contains a large number of ether bonds on the side chains. Under the attack of free radicals, it is easy to cause the conductivity of the membrane to drop sharply, which is not conducive to the long-term operation of the membrane. In addition, Nafion @The poor barrier rate for fuel, especially methanol, will lead to catalyst poisoning, fuel waste and reduced coulombic efficiency. In addition, its manufacturing process is complicated, involving multiple fluorine reactions and low synthetic safety, which further hinders its large-scale development. @ These shortcomings of the series of membranes not only limit the commercialization process of direct methanol fuel cells, but also pose a potential threat to the environment and human health. To this end, the present invention proposes a natural product derived algae polyelectrolyte membrane and a preparation method and application thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a natural product derived algae polyelectrolyte membrane and a preparation method and application thereof, aiming to solve the problems raised in the above background technology.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The method for preparing a natural product-derived algae polyelectrolyte membrane comprises the following steps:

[0007] Step 1, preparation of sulfonated sodium alginate;

[0008] Dissolving sodium alginate powder in deionized water and stirring until completely dissolved to obtain a sodium alginate aqueous solution; adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) / N-hydroxysuccinimide (NHS) to the sodium alginate aqueous solution, and adding cysteine ​​to the mixture; adjusting the pH value of the system, stirring at room temperature and completing the reaction; dialyzing, drying and oxidizing the sample after the reaction to obtain sulfonated sodium alginate powder;

[0009] Step 2, preparation of sulfonated diatomite;

[0010] The diatomite powder is added to a sulfuric acid solution for purification, and after stirring, it is completely washed with deionized water and dried; the purified diatomite powder is mixed with an ethanol aqueous solution containing a KH-550 solution, heated and stirred, and after stirring, it is completely washed with deionized water and dried to obtain a diatomite powder grafted with KH-550; the diatomite powder grafted with KH-550 is added to a cysteine ​​solution containing EDC / NHS; the mixture is oxidized with a hydrogen peroxide solution, and after oxidation, it is completely washed with deionized water and dried to obtain a sulfonated diatomite powder;

[0011] Step 3, preparation of natural product derived algae polyelectrolyte membrane;

[0012] The dried sulfonated sodium alginate powder obtained in step 1 is dissolved in deionized water to form a casting solution with a concentration of 2.0%; the sulfonated diatomaceous earth powder obtained in step 2 is added to the casting solution in proportion and stirred for 24 hours; the uniformly dispersed mixture is slowly poured onto a horizontal glass plate and dried at room temperature to form a membrane; the membrane is soaked in a glycerol / calcium chloride solution for 30 minutes and then in a sulfuric acid solution for 30 minutes; after washing away the residual solvent with deionized water, it is heated at 100°C for 2 hours to obtain a natural product-derived algae polyelectrolyte membrane.

[0013] Furthermore, the specific process of step 1 is as follows:

[0014] 1.0 g of sodium alginate was dissolved in deionized water and stirred until completely dissolved to obtain 100 mL of a 1% w / v sodium alginate aqueous solution; 50 mM EDC and 100 mM NHS were added to the sodium alginate aqueous solution, and the solution was stirred for 1 hour; 2.0 g of cysteine ​​was added to the solution, the pH was adjusted to 4.0, and the solution was continuously stirred for 2 hours at room temperature, and then the pH was adjusted to 6.0, and the reaction was continued for 1 hour; after the reaction was completed, the reacted sample was dialyzed and dried to obtain sodium thioalginate; the sodium thioalginate was oxidized with 1% hydrogen peroxide for 12 hours; the oxidized sample was dried at 60° C. to obtain sulfonated sodium alginate powder.

[0015] Furthermore, the specific process of step 2 is as follows:

[0016] 10 g of diatomaceous earth powder was purified by adding it to a 5M sulfuric acid solution, stirred at 100°C for 4 hours, and then completely washed with deionized water and dried at 60°C. At the same time, 10% of the KH-550 solution was added to a 95% ethanol aqueous solution at pH = 4 and stirred; the purified diatomaceous earth powder was mixed with the ethanol aqueous solution containing the KH-550 solution, heated to 80°C and stirred for 2 hours, then washed with deionized water and dried at 60°C to obtain a diatomaceous earth powder grafted with KH-550; the diatomaceous earth powder grafted with KH-550 was added to a Cys solution with a concentration of 558 mM and pH = 4 activated with 50 mM EDC and 100 mM NHS; the mixture was stirred at room temperature for 2 hours, and 3% H 2 O 2 The mixture was oxidized by the solution, and after oxidation, it was washed with deionized water and dried at 60° C. to obtain sulfonated diatomaceous earth powder.

[0017] Further, when preparing the natural product derived algae polyelectrolyte membrane APEM-4, the specific process of step 3 is as follows:

[0018] The dried sulfonated sodium alginate powder obtained in step 1 is dissolved in deionized water to form a 2.0% casting solution; the sulfonated diatomaceous earth powder obtained in step 2 is added to the casting solution at a ratio of 4wt% of the sulfonated sodium alginate powder, and stirred for 24 hours; the evenly dispersed mixture is slowly poured onto a horizontal glass plate, and dried at room temperature to form a membrane; the membrane is soaked in a glycerol / calcium chloride solution for 30 minutes, and then soaked in a 1M sulfuric acid solution for 30 minutes, and after washing away the residual solvent with deionized water, it is heated at 100°C for 2 hours to obtain a natural product derived algae polyelectrolyte membrane APEM-4.

[0019] The natural product derived algae polyelectrolyte membrane is prepared according to the method for preparing the natural product derived algae polyelectrolyte membrane described above.

[0020] According to the above-mentioned application of the natural product derived algae polyelectrolyte membrane as a proton exchange membrane in a direct methanol fuel cell.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention has successfully developed an algae polyelectrolyte membrane based on natural products, which has shown superior performance over traditional Nafion in direct methanol fuel cells. @ The performance of the 117 membrane not only improves the open circuit voltage and maximum power density, but also significantly reduces production costs, reduces environmental pollution, simplifies the preparation process, and avoids the production of toxic intermediates, effectively solving the problem of high methanol fuel permeability, and provides new ideas for the design of high-performance, low-cost, and environmentally friendly proton exchange membranes. It is of great significance to the high-value utilization of biomass resources, environmental protection, and social sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a process flow chart of the present invention.

[0024] Figure 2 The natural product derived algae polyelectrolyte membrane of the present invention is combined with Nafion @ Comparison of single cell performance of 117 membranes. DETAILED DESCRIPTION

[0025] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of the present invention. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials can be obtained from commercial sources unless otherwise specified.

[0026] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0027] Example 1, preparation of sulfonated sodium alginate;

[0028] First, 1.0g of sodium alginate (SA) was dissolved in deionized water and stirred until completely dissolved to obtain 100mL of sodium alginate aqueous solution with a concentration of 1% w / v. Then, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) (50mM) / N-hydroxysuccinimide (NHS) (100mM) was added and the solution was stirred for 1h to activate the carboxyl group of SA. Then, 2.0g of cysteine ​​(Cys) was added to the solution, the pH was adjusted to about 4.0, and it was stirred continuously at room temperature for 2h. Then, the pH was adjusted to about 6.0 and the reaction was continued for 1h. After the reaction was completed, the reacted sample was dialyzed and dried to obtain sodium thioalginate (TSA); TSA was treated with 1% hydrogen peroxide (H 2 O 2 ) was oxidized for 12 h; finally, the oxidized sample was dried at 60°C to obtain sulfonated sodium alginate powder (MSA).

[0029] Example 2: Preparation of sulfonated low-grade diatomite;

[0030] 10 g of low-grade diatomaceous earth powder (DE) was added to sulfuric acid (H 2 SO 4 ) solution (5M), stirred at 100°C for 4h, washed completely with deionized water after stirring, and dried at 60°C. At the same time, KH-550 solution (10%) was added to 95% ethanol aqueous solution (pH=4) and stirred. The purified diatomaceous earth powder was mixed with the ethanol aqueous solution added with KH-550 solution, heated to 80°C and stirred for 2h. Then, it was washed with deionized water and dried at 60°C to obtain the diatomaceous earth powder grafted with KH-550, which was added to the Cys solution (558mM, PH=4) activated with EDC (50mM) / NHS (100mM). Then, the mixture was stirred at room temperature for 2h and activated with 3% H 2 O 2 The solution was oxidized, washed with deionized water, and dried at 60° C. to obtain sulfonated diatomaceous earth powder (MDE).

[0031] Example 3: Preparation of natural product derived algae polyelectrolyte membrane MSA:

[0032] The dried sulfonated sodium alginate powder obtained in Example 1 was dissolved in deionized water to form a casting solution (2.0%), which was slowly poured onto a horizontal glass plate and dried at room temperature. The membrane was soaked in a glycerol / calcium chloride solution for 30 minutes, and then soaked in a 1M sulfuric acid solution for 30 minutes; after washing away the residual solvent with deionized water, it was heated at 100°C for 2 hours to obtain an MSA membrane.

[0033] Example 4: Preparation of natural product derived algae polyelectrolyte membrane APEM-2:

[0034] The dried sulfonated sodium alginate powder obtained in Example 1 was dissolved in deionized water to form a casting solution (2.0%). The sulfonated diatomaceous earth powder obtained in Example 2 was added to the casting solution at a ratio of 2 wt% of the sulfonated sodium alginate powder, stirred for 24 h, and the uniformly dispersed mixture was slowly poured onto a horizontal glass plate and dried at room temperature. The membrane was soaked in a glycerol / calcium chloride solution for 30 min, and then soaked in a 1 M sulfuric acid solution for 30 min. After washing away the residual solvent with deionized water, it was heated at 100° C. for 2 h to obtain an APEM-2 membrane.

[0035] Example 5: Preparation of natural product derived algae polyelectrolyte membrane APEM-4:

[0036] The dried sulfonated sodium alginate powder obtained in Example 1 was dissolved in deionized water to form a casting solution (2.0%). The sulfonated diatomaceous earth powder obtained in Example 2 was added to the casting solution at a ratio of 4 wt% of the sulfonated sodium alginate powder, stirred for 24 h, and the uniformly dispersed mixture was slowly poured onto a horizontal glass plate and dried at room temperature. The membrane was soaked in a glycerol / calcium chloride solution for 30 min, and then soaked in a 1M sulfuric acid solution for 30 min. After washing away the residual solvent with deionized water, it was heated at 100°C for 2 h to obtain an APEM-4 membrane.

[0037] Example 6: Preparation of natural product derived algae polyelectrolyte membrane APEM-6:

[0038] The dried sulfonated sodium alginate powder obtained in Example 1 was dissolved in deionized water to form a casting solution (2.0%). The sulfonated diatomaceous earth powder obtained in Example 2 was added to the casting solution at a ratio of 6 wt% of the sulfonated sodium alginate powder, stirred for 24 h, and the uniformly dispersed mixture was slowly poured onto a horizontal glass plate and dried at room temperature. The membrane was soaked in a glycerol / calcium chloride solution for 30 min, and then soaked in a 1M sulfuric acid solution for 30 min. After washing away the residual solvent with deionized water, it was heated at 100°C for 2 h to obtain an APEM-6 membrane.

[0039] Example 7: Preparation of natural product derived algae polyelectrolyte membrane APEM-8:

[0040] The dried sulfonated sodium alginate powder obtained in Example 1 was dissolved in deionized water to form a casting solution (2.0%). The sulfonated diatomaceous earth powder obtained in Example 2 was added to the casting solution at a ratio of 8 wt% of the sulfonated sodium alginate powder, stirred for 24 h, and the uniformly dispersed mixture was slowly poured onto a horizontal glass plate and dried at room temperature. The membrane was soaked in a glycerol / calcium chloride solution for 30 min, and then soaked in a 1M sulfuric acid solution for 30 min. After washing away the residual solvent with deionized water, it was heated at 100°C for 2 h to obtain an APEM-8 membrane.

[0041] In terms of price, the commonly used Nafion @ Membranes cost about $1,000 per square meter, while the natural product-derived algae polyelectrolyte membranes of the present invention are expected to cost less than $100 per square meter.

[0042] Application Example 1: In terms of performance, in order to more directly verify the feasibility of using natural product-derived algae polyelectrolyte membrane in direct methanol fuel cells, a membrane electrode assembly was prepared by hot pressing at a pressure of 10 MPa and a temperature of 120°C. The cathode and anode catalysts were Pt / C (40 wt% Pt) and PtRu / C (40 wt% Pt and 20 wt% Ru), respectively. -1 and 30 mL min -1 Aqueous methanol (2 M) and O were supplied to the anode and cathode at a flow rate of 2 The single cell performance of the membrane was measured at 80°C. It was compared with Nafion, the most widely used proton exchange membrane. @ 117 membranes were compared. The results showed that ( Figure 2 ), Nafion @ The open circuit voltage and maximum power density of 117 are only 0.72 V and 61 mW cm, respectively. -2 , while the open circuit voltage and maximum power density of the APEM-4 of the present invention are 0.78 V and 65 mW cm -2 , demonstrating its potential value in direct methanol fuel cells.

[0043] In summary, the present invention has successfully developed an algae polyelectrolyte membrane based on natural products, which has shown superior performance to conventional Nafion in direct methanol fuel cells. @ The performance of the 117 membrane not only improves the open circuit voltage and maximum power density, but also significantly reduces production costs, reduces environmental pollution, simplifies the preparation process, and avoids the production of toxic intermediates, effectively solving the problem of high methanol fuel permeability, and provides new ideas for the design of high-performance, low-cost, and environmentally friendly proton exchange membranes. It is of great significance to the high-value utilization of biomass resources, environmental protection, and social sustainable development.

[0044] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a natural product derived algae polyelectrolyte membrane, characterized in that: The following steps are involved: Step 1, preparation of sulfonated sodium alginate; Dissolving sodium alginate powder in deionized water and stirring until completely dissolved to obtain a sodium alginate aqueous solution; adding EDC / NHS to the sodium alginate aqueous solution and adding cysteine ​​to the mixture; adjusting the pH value of the system, stirring at room temperature and completing the reaction; dialyzing, drying and oxidizing the sample after the reaction to obtain sulfonated sodium alginate powder; Step 2, preparation of sulfonated diatomite; The diatomite powder is added to a sulfuric acid solution for purification, and after stirring, it is completely washed with deionized water and dried; the purified diatomite powder is mixed with an ethanol aqueous solution containing a KH-550 solution, heated and stirred, and after stirring, it is completely washed with deionized water and dried to obtain a diatomite powder grafted with KH-550; the diatomite powder grafted with KH-550 is added to a cysteine ​​solution containing EDC / NHS; the mixture is oxidized with a hydrogen peroxide solution, and after oxidation, it is completely washed with deionized water and dried to obtain a sulfonated diatomite powder; Step 3, preparation of natural product derived algae polyelectrolyte membrane; The dried sulfonated sodium alginate powder obtained in step 1 is dissolved in deionized water to form a casting solution; the sulfonated diatomaceous earth powder obtained in step 2 is added to the casting solution in proportion and stirred for 24 hours; the uniformly dispersed mixture is slowly poured onto a horizontal glass plate and dried at room temperature to form a membrane; the membrane is soaked in a glycerol / calcium chloride solution for 30 minutes and then in a sulfuric acid solution for 30 minutes; after washing away the residual solvent with deionized water, it is heated at 100°C for 2 hours to obtain a natural product-derived algae polyelectrolyte membrane.

2. The method for preparing a natural product derived algae polyelectrolyte membrane according to claim 1, characterized in that: The specific process of step 1 is as follows: 1.0 g of sodium alginate was dissolved in deionized water and stirred until completely dissolved to obtain 100 mL of a 1% w / v sodium alginate aqueous solution; 50 mM EDC and 100 mM NHS were added to the sodium alginate aqueous solution, and the solution was stirred for 1 hour; 2.0 g of cysteine ​​was added to the solution, the pH was adjusted to 4.0, and the solution was continuously stirred for 2 hours at room temperature, and then the pH was adjusted to 6.0, and the reaction was continued for 1 hour; after the reaction was completed, the reacted sample was dialyzed and dried to obtain sodium thioalginate; the sodium thioalginate was oxidized with 1% hydrogen peroxide for 12 hours; the oxidized sample was dried at 60° C. to obtain sulfonated sodium alginate powder.

3. The method for preparing a natural product derived algae polyelectrolyte membrane according to claim 1, characterized in that: The specific process of step 2 is as follows: 10g of diatomaceous earth powder was added to a 5M sulfuric acid solution for purification, stirred at 100°C for 4h, and then completely washed with deionized water and dried at 60°C. At the same time, a 10% KH-550 solution was added to a 95% ethanol aqueous solution with a pH of 4 and stirred; the purified diatomaceous earth powder was mixed with the ethanol aqueous solution containing the KH-550 solution, heated to 80°C and stirred for 2h, then washed with deionized water and dried at 60°C to obtain a diatomaceous earth powder grafted with KH-550; the diatomaceous earth powder grafted with KH-550 was added to a Cys solution with a concentration of 558mM and a pH of 4 activated with 50mM EDC and 100mM NHS; the mixture was stirred at room temperature for 2h, and the mixture was oxidized with a 3% H2O2 solution, washed with deionized water and dried at 60°C after oxidation to obtain a sulfonated diatomaceous earth powder.

4. The method for preparing a natural product derived algae polyelectrolyte membrane according to claim 1, characterized in that: When preparing the natural product derived algae polyelectrolyte membrane APEM-4, the specific process of step 3 is as follows: The dried sulfonated sodium alginate powder obtained in step 1 is dissolved in deionized water to form a 2.0% casting solution; the sulfonated diatomaceous earth powder obtained in step 2 is added to the casting solution at a ratio of 4wt% of the sulfonated sodium alginate powder, and stirred for 24 hours; the evenly dispersed mixture is slowly poured onto a horizontal glass plate, and dried at room temperature to form a membrane; the membrane is soaked in a glycerol / calcium chloride solution for 30 minutes, and then soaked in a 1M sulfuric acid solution for 30 minutes, and after washing away the residual solvent with deionized water, it is heated at 100°C for 2 hours to obtain a natural product derived algae polyelectrolyte membrane APEM-4.

5. A natural product derived algae polyelectrolyte membrane prepared according to the method for preparing a natural product derived algae polyelectrolyte membrane according to any one of claims 1 to 4.

6. Use of the natural product derived algae polyelectrolyte membrane according to claim 5 as a proton exchange membrane in a direct methanol fuel cell.

Citation Information

Cited By

  • Hard-water-resistant multilayer composite proton exchange membrane as well as preparation method and application thereof

    CN120854592A